Prins cyclization-mediated stereoselective synthesis of tetrahydropyrans and dihydropyrans: an inspection of twenty years - Budakoti, Asha (Beilstein J Org Chem, 2021)
Functionalized tetrahydropyran (THP) rings are important building blocks and ubiquitous scaffolds in many natural products and active pharmaceutical ingredients (API). Among various established methods, the Prins reaction has emerged as a powerful technique in the stereoselective synthesis of the tetrahydropyran skeleton with various substituents, and the strategy has further been successfully applied in the total synthesis of bioactive macrocycles and related natural products. In this context, hundreds of valuable contributions have already been made in this area, and the present review is intended to provide the systematic assortment of diverse Prins cyclization strategies, covering the literature reports of the last twenty years (from 2000 to 2019), with an aim to give an overview on exciting advancements in this area and designing new strategies for the total synthesis of related natural products.